The Role of Brand Trust in Mediating the Effect of Product Differentiation and Price on Repurchase Decision at Kopi Kenangan Surabaya - Laurent Regina Anjani; Sri Tjondro Winarno; Taufik Setyadi; Gyska Indah Harya (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The rapid growth of the coffee shop industry in Indonesia has intensified competition among coffee shop brands, encouraging companies to strengthen repurchase decisions through product differentiation, pricing strategies, and brand trust. This study aims to analyze the role of brand trust in mediating the effect of product differentiation and price on repurchase decision at Kopi Kenangan Surabaya. This study employed a quantitative approach using Structural Equation Modeling – Partial Least Squares (SEM-PLS) with WarpPLS 8.0. The respondents consisted of 200 actual customers of Kopi Kenangan in Surabaya selected using purposive sampling techniques from Kopi Kenangan Merr, Ahmad Yani, BP Margorejo, and The Square outlets. The results indicate that product differentiation significantly affects repurchase decision (β = 0.120) and brand trust (β = 0.650), while price significantly affects brand trust (β = 0.660) but does not significantly affect repurchase decision directly (β = 0.100). Furthermore, brand trust significantly affects repurchase decision (β = 0.820) and mediates the relationship between product differentiation, price, and repurchase decision. These findings indicate that consumers consider brand trust before making long-term repurchase decisions toward coffee shop products.